Экспертная оценка проблем при оказании эндодонтического лечения (Эндодонтия Today)
Mistakes and complications in the implementation of therapeutic manipulation is not rare. The article analyzes the work of the dentist when providing dental care. The irregularities during the endodontic treatment, as well as keeping medical records, ethics and deontology, and possibility of avoiding claims from patients were noted.